Machine Learning in Translation Corpora Processing - Wolk, Krzysztof (CRC Press, 2019)
This book reviews ways to improve statistical machine speech translation between Polish and English. The main objective of this book to develop an automatic and robust Polish to English translation system to meet specific translation requirements and to develop bilingual textual resources by mining comparable corpora.